Comparative analysis of modular outer rotor and modular inner rotor permanent magnet flux switching machine - Roshada Ismail; Erwan Sulaiman; Syed Muhammad Naufal Syed Othman; Nur Afiqah Mostaman; Irfan Ali Soomro (Institute of Advanced Engineering and Science, 2026)
A modular rotor is an advanced design in electric motor (EM) technology, offering enhanced performance and efficiency for various applications. Its segmented structure allows for optimized magnetic flux paths, reducing iron losses and improving energy efficiency. The modular rotors can be classified into modular inner rotors and modular outer rotors (ORs). While both have their applications, modular inner rotor permanent magnet flux switching machines (PMFSMs) face limitations, including lower torque density, inefficient magnetic flux operation, and reduced cooling capability, making them less suitable for high-torque applications. This paper presents an analysis of the comparison between a new modular OR and a modular inner rotor PMFSM. The outer OR-PMFSM offers higher torque density due to more efficient magnetic flux positioning, resulting in a better torque-to weight ratio. The design and analysis are conducted using JMAG designer version 18 under no-load and load conditions to test the proposed design's effectiveness. Hence, the suggested design obtained an increment of torque and power of 6.06% and 5.4%, respectively. In conclusion, the modular OR produces higher torque and power than the modular OR. The proposed motor can be very useful in electric bike applications for practical high performance and low cost.